KAJIAN DOSIS SERBUK CANGKANG TELUR DAN PUPUK KNO3 TERHADAP PERTUMBUHAN DAN HASIL TIMUN SURI (Cucumis melo L.) : Kata kunci: Cangkang Telur, KNO3, Timun Suri, Pertumbuhan, Hasil - Pandu Prayoga; Sartono Joko Santosa; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
Study of the dose of egg shell powder and KNO3 fertilizer on the growth and yield of lemon cucumber (Cucumis melo L.). was carried out from 24 May to 25 July 2022, which was completed in the Tohudan Food Crops and Horticultural Seed Plantation in Karanganyar. This study's objective was to examine various doses of eggshell powder and KNO3 manure on the development and yield of lemon cucumber. This study utilized a completely randomized design (CRD) with a 4 x 4 factorial structure so that 16 treatments with 3 replications were obtained and each treatment had 1 sub-replication, so there were a total of 96 polybags. The two factors studied included Dosage of Eggshell Powder Fertilizer (P): P0 control, P1 eggshell fertilizer 6.25 g/polybag, P2 eggshell fertilizer 12.50 g/polybag, P3 eggshell fertilizer 18.75 g/polybag and types of drought stress. (K) : K0 control, K1 KNO3 fertilizer 2.5 g/polybag, K2 KNO3 fertilizer 5 g/polybag, K3 KNO3 fertilizer 7.5 g/polybag. The observed parameters included plant length, stem diameter, number of fruits, their length, and their diameter, as well as the number of male and female flowers. An Honest Significant Difference Test at the 5% level was followed by an analysis of the data using Analysis of Variance. The results of this research that ⁽¹⁾Treatments the dose of eggshell fertilizer (P) had a significant effect on fruit weight. ²⁾ Treatment dose of KNO3 (K) fertilizer had a significant effect on plant length, stem diameter, number of male flowers, fruit weight, fruit length, and fruit diameter, but not in the number of female flowers or the number of fruits per plant. ⁽³⁾Fruit weight was significantly affected by the combination of treatments. Interaction between 6.50 g/polybag egg shell powder and 5 g/polybag KNO3 fertilizer (P1K2) produced the highest fruit weight, namely 810,67 grams.